“ANNA KARENINA”- T. STOPPARD VS. L. TOLSTOY - Gurina, EKATERINA (Journal of Education Culture and Society, 2018)
Aim. The aim of the research is to compare Konstantin Levin’s function in the film Anna Karenina(2012) by Joe Wright, the script written by Tom Stoppard and the novel Anna Kareninaby Leo Tolstoy and to determine how much his figure was changed in the film adaptation under the influence of the scriptwriter’s and director’s stance.Methods. The subjects of the study were the film Anna Karenina (2012) by Joe Wright, the script written by Tom Stoppard and the novel Anna Karenina by Leo Tolstoy. They are analysed with the use of the theory of script writing, different types of character classifications and the text corpus analysis, taking into account the cultural, historical and economic features of scriptwriting and film production.Results. The analysis shows that Konstantin Levin’s function of the second protagonist that is characteristic for the novel is further developed in the screenplay but is omitted in the film. The discrepancies with the source book and the screenplay are caused by the influence of the film director during the film production.Conclusions. Even though the study considers the texts that are closely interrelated, the individual author’s stance influences the text of the screenplay so much that it gives us an opportunity to call Tom Stoppard, the scriptwriter, a writer in the full sense of the word.